Correlation between teacher competence and the self-efficacy of secondary school teachers - Shukla, Jyoti (Journal of Interdisciplinary Studies in Education, 2024)
The purpose of this study was to compare the different levels of teacher competence and self-efficacy among secondary school teachers. A comparative survey method for descriptive research was used. A total of 147 secondary school teachers were selected through a random sampling method. Analysis of variance was used for data analysis. The key finding of this study is that among male and female teachers with high, moderate, and low competency levels, there are no significant differences in self-efficacy. Government teachers show no significant differences in self-efficacy with respect to their competence levels, but private teachers show an apparent pattern. Private teachers differ only in terms of high and low levels of self-efficacy; neither high nor medium self-efficacy levels differ from one another.